Celebrating Rose Watkins' 64th Birthday-207 Geneva Avenue - Watkins, Howard::::::::: (1983)
Robin Watkins, Christine Watkins wearing long black slacks, Adam Watkins, friend on bed in studio unit Round Cherokee hanging shield on wall